Design principle of cylindrical superdirective antenna. (18th September 2019) - Chen, Wan; Fu, Jiahui; Wu, Qun; Lv, Bo
Abstract: We propose the design principle of a superdirective antenna with needle-like radiation based on multi-layered dielectric cylinder. The electromagnetic fields and far-field directivity of superdirective antenna are calculated. The radiation mechanisms of the superdirective antenna are illustrated by multi-layered asymmetric SPR phenomenon. A nonlinear searching algorithm is utilized to calculate the design parameters of the antenna. A series of constraint conditions on the design parameters are derived from the phenomenon. The constraint conditions restrict the initial values of optimization in a limited solution space, and act as a guidance on the optimizing process and improves the convergence and quality of optimization.